Geological solutions concluded by petroleum geochemical data in Western Greece - Rigakis, N.; Karakitsios, V.; Marnelis, F.; Sotiropoulos, Sp. (Bulletin of the Geological Society of Greece, 2013)
A detailed petroleum geochemical study has been performed in the previous years in the Western Greece. Several source rock horizons have been identified, the oil window has been calculated for the most significant sub-basins and the oil correlation study has distinguished the different oil groups of the area, generated from different hydrocarbon sources. These results are very significant and useful for the oil exploration. But, further to these, some more geochemical observations can also be very important on solving some geological problems of the area. - A major problem is the deposition and preservation of the organic matter in the Western Greece. - The dolomitization in relation with the oil generation is also an issue. - Another issue is the calculation of the eroded overburden formations thickness. - The Paleogeothermal gradient determination is also very important. The last two parameters are absolutely necessary for organic matter maturity calculations. The study of all the above parameters completes the geochemical study of the Western Greece, and in relation with other geological studies can provide solutions in the petroleum exploration of the area.